Characterization of thermoelectric generators for voltage control circuits in low power electronic devices - Mohamed, Ramizi; Mohd Annuar, Khalil Azha; Yusof, Yushaizad; Kassim, Muhammad Nasrullah (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research explores the characterization and development of a circuit capable of powering low-power electronic devices using thermoelectric generators (TEG). As global interest in renewable energy sources grows, alternatives such as hydroelectric and solar power have gained attention for their environmental benefits and availability. However, the challenge of energy loss due to insufficient heat persists. TEGs are electronic devices that can convert various forms of thermal energy, including waste heat, into electrical energy. Utilizing the Seebeck effect, TEGs generate voltage when there is a temperature difference between their hot and cold plates. The greater the temperature difference between the two sides, the higher the voltage production. Several factors influence TEG performance, including the construction materials, such as Bi2 Te3, and the surface area available for heating. This research aims to identify the best TEG and its characterization that can increase the temperature difference range to produce higher output voltage. Furthermore, it seeks to determine the most suitable type of TEG and the optimal circuit construction for generating sufficient output voltage to power low-power electronic devices. This includes determining the appropriate number of TEG units, the use of a boost-type DC-DC converter, and the number of filter circuits required to smooth the output voltage. Finally, the research aims to identify the optimal voltage, current, and power required to operate low-power electronic devices, such as fans, buzzers, and LEDs. Experimental results show that three TEG units produce a maximum voltage of 0.927V, a current as high as 71.2mA and a highest power of 50.694mW at a surface temperature of 80°C. The efficient energy conversion and voltage stability observed affirm the viability of TEGs as alternative power sources for small-scale sensing systems and IoT applications.